Case of Indonesia: government bond issuer investor relations strategy - Firman Darwis; Sudarso Kaderi Wiryono; Ahmad Danu Prasetyo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study elaborates Indonesia's investor relations activities in building and maintaining positive perceptions of the Indonesian economy as a debt issuer in international financial markets. The study begins with several theories in investor relations, communication strategies, and investor relations current practices in Indonesia. By referring to various theories related to investor relations, an assessment is carried out that focuses on strengthening efforts in preparing the framework for the communication strategy of investor relations in the Republic of Indonesia. In addition, this study also aims to produce a communication strategy framework that can be applied in preparing sharper, focused, and goal-oriented work programs and communication strategies. This study resulted in a framework for strengthening investor relations strategies in Indonesia which have taken into account factors according to investor relations theory and the strategic environment that has become the concern of the international financial community.